HPLC-MS profiling and protective potential of the defatted aqueous methanol extract of two Syzygium species against cadmium chloride-induced nephrotoxicity in rats - Fatma A. Moharram; Sahar S. Salem; Samah Shabana; Elsayed K. El-Sayed; Shimaa K. Mohamed; Mohamed A. Khattab; Kuei-Hung Lai; Asmaa A. Ahmed; Heba E. Elsayed (PLoS ONE, 2025)
Cadmium (Cd), a highly toxic heavy metal, is used in food and agricultural products while displaying nephrotoxicity to animals and humans. The genus Syzygium (Myrtle family) is rich in precious phenolic metabolites with various therapeutic values. This study investigated the phenolic content and the therapeutic potential of the defatted 80% aqueous methanol extract (DE) of S. malaccense and S. samarangense leaves against Cd-induced kidney injury in rats for the first time. High-performance liquid chromatography-Mass spectrometry (HPLC-MS), in addition to Folin-Ciocalteu and aluminium chloride colourimetric methods, depicted the phenolic metabolites, total phenolic content, and total flavonoid content, respectively. The nephroprotective effect was investigated using fifty-six female Sprague Dawley rats divided into eight groups: control group, CdCl2-treated group (3 mg/kg/i.p/7 days), and three groups of each species treated with the DE (250, 500, and 1000 mg/kg/o.p., respectively). The phytochemical analysis revealed the richness of S. samarangense DE by phenolic and flavonoid content over S. malaccense. The HPLC-MS showed the tentative identification of sixty-two compounds, in positive and negative ionization modes, belonging to phenolic acids (1−6), flavonoids (7−52), and miscellaneous compounds (53−62). Both extracts were considered safe up to 5 g/kg. At the maximum tested dose (100 mg/Kg), the DEs significantly (p < 0.001) boosted the levels of antioxidant markers by 3.3–6 fold, lessened the inflammatory indicators by 66.8%−75.1%, and reduced the apoptotic parameters by 45.4–73.3%, compared to the CdCl2-treated group. Additionally, the DEs maintained the mitochondrial function and inhibited autophagy via decreasing adenosine monophosphate-activated protein kinase by 49.2%−50.6%, and baclin-1 by 49.5%−56.1%. Additionally, the DEs increased the mammalian target of rapamycin (mTOR) by 4.7–4.9 fold. Additionally, the DE ameliorated CdCl2-induced elevations in serum ALT and AST, indicating a protective effect against systemic toxicity. Ultimately, the DE of S. malaccense and S. samarangense protect against Cd-induced nephrotoxicity that may be correlated to their abundant phenolic content. However, selecting suitable formulations and implementing clinical studies are among the future directions.